2019
DOI: 10.1101/541383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic programming of antigen cross-presentation in IRF4-expressing human Langerhans cells

Abstract: Langerhans cells (LCs) in the epidermis present MHC I and MHC II-restricted antigens thereby priming either CD8 or CD4 T cell immune responses. The genomic programs and transcription factors regulating antigen presentation in LCs remain to be elucidated. We show human LCs are highly efficient in MHC I-antigen cross-presentation but lack the transcription factor IRF8 that is critical in dendritic cells. LC migration from the epidermis enhances their ability to cross-present antigens and is accompanied by the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 102 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Supporting the association between immunocompetence and ability to induce tolerance, LC migration out of the epidermis resulted in an even greater ability to induce Tregs than immunocompetent (S2) steadystate LCs. Analysis of single LC transcriptomes confirmed that migratory LCs are mature and characterised by upregulation of MHC II molecules, co-stimulatory molecules (CD80 and CD86) and chemokine receptors (CCR7), indicating readiness for migration to local lymph nodes, mediating interaction with T cells to promote adaptive immune responses 39,40,41,19,27,28 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Supporting the association between immunocompetence and ability to induce tolerance, LC migration out of the epidermis resulted in an even greater ability to induce Tregs than immunocompetent (S2) steadystate LCs. Analysis of single LC transcriptomes confirmed that migratory LCs are mature and characterised by upregulation of MHC II molecules, co-stimulatory molecules (CD80 and CD86) and chemokine receptors (CCR7), indicating readiness for migration to local lymph nodes, mediating interaction with T cells to promote adaptive immune responses 39,40,41,19,27,28 .…”
Section: Discussionmentioning
confidence: 95%
“…To explore further the link between LC activation status and tolerance induction, we sought to investigate the effect of in vitro migration from epidermal sheets on LCs tolerogenic characteristics and their molecular profile. We and others have previously shown that LCs, which have migrated out of the epidermis are more immune activated and primed to mediating T cell responses 6,27,28 . Therefore, we sought to compare the capability of both steady-state LC and migrated LC to prime naïve CD4 T cells towards a tolerogenic phenotype.…”
Section: Migration Enhances Tolerogenic Abilities Of Immunocompetent Lcsmentioning
confidence: 92%
See 2 more Smart Citations